Syndrome of Reversible Cardiogenic Shock and Left Ventricular Ballooning in Obstructive Hypertrophic Cardiomyopathy - Mark V. Sherrid; Daniel G. Swistel; Iacopo Olivotto; Maurizio Pieroni; Omar Wever‐Pinzon; Katherine Riedy; Richard G. Bach; Mustafa Husaini; Sharon Cresci; Alex Reyentovich; Daniele Massera; Martin S. Maron; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background Cardiogenic shock from most causes has unfavorable prognosis. Hypertrophic cardiomyopathy (HCM) can uncommonly present with apical ballooning and shock in association with sudden development of severe and unrelenting left ventricular (LV) outflow obstruction. Typical HCM phenotypic features of mild septal thickening, outflow gradients, and distinctive mitral abnormalities differentiate these patients from others with Takotsubo syndrome, who have normal mitral valves and no outflow obstruction. Methods and Results We analyzed 8 patients from our 4 HCM centers with obstructive HCM and abrupt presentation of cardiogenic shock with LV ballooning, and 6 cases reported in literature. Of 14 patients, 10 (71%) were women, aged 66±9 years, presenting with acute symptoms: LV ballooning; depressed ejection fraction (25±5%); refractory systemic hypotension; marked LV outflow tract obstruction (peak gradient, 94±28 mm Hg); and elevated troponin, but absence of atherosclerotic coronary disease. Shock was managed with intravenous administration of phenylephrine (n=6), norepinephrine (n=6), β‐blocker (n=7), and vasopressin (n=1). Mechanical circulatory support was required in 8, including intra‐aortic balloon pump (n=4), venoarterial extracorporeal membrane oxygenation (n=3), and Impella and Tandem Heart in 1 each. In refractory shock, urgent relief of obstruction by myectomy was performed in 5, and alcohol ablation in 1. All patients survived their critical illness, with full recovery of systolic function. Conclusions When cardiogenic shock and LV ballooning occur in obstructive HCM, they are marked by distinctive anatomic and physiologic features. Relief of obstruction with targeted pharmacotherapy, mechanical circulatory support, and myectomy, when necessary for refractory shock, may lead to survival and normalization of systolic function.